Penentuan persentase uptake radiofarmaka Tc99m Sulfur Colloid pada sidik hati (Liver scan) - Istifadatun Ni’amah; Wahyu Setiabudi; Fadil Nazir (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Based on data from the World Health Organization, showed that liver disease in Indonesia is in endemic high ranks. Early diagnosis of liver disease is very necessary for prevention and minimize the risk of liver disease. Research has been conducted on 28 patients on the biodistribution test of the liver scan using in vivo nuclear medicine technique that aims to determine the accumulation of counts Tc99m Sulfur Colloid in the body's metabolism, the percentage uptake activity in the heart, spleen, kidney, bladder, and liver as the target organ. The study was conducted using Tc99m obtained from elution of Mo99 generator and mixed with sulfur colloid. Tc99m allows a radiopharmaceutical can be detected and known location and sulfur colloid to determine where the target of radiopharmaceutical is accumulated. Liver scan is performed by injecting Tc99m Sulfur Colloid intravenously into the patient's arm as much as 2- 6mCi. Furthermore, the anterior posterior planar imaging in abdominal cavity at 5 minutes and 1 hour after injection of the patient by using a gamma camera. Determining the state of liver function can be seen from the percentage uptake activity at 5 minutes and 1 hour, the shape and size of the heart which can be evaluated from the image obtained. Biodistribution of Tc99m Sulfur Colloid showed a high percentage of the liver after 5 minutes and 1 hour. Based on the value percentage uptake activity obtained, there were 18 patients with a normal liver and 10 patients with abnormal liver. Keywords: Tc99m Sulfur Colloid, liver scan, nuclear medicine, gamma camera